BUNDLE FOR THE PREVENTION OF PRESSURE INJURIES ASSOCIATED WITH MEDICAL DEVICES IN OBESE PATIENTS - Andrade, Vanusa Silva do Nascimento; Sebold, Luciara Fabiane (Cogitare Enfermagem, 2023)
Objective: to build and validate a Bundle for the prevention of pressure injuries associated with medical devices in obese people in intensive care. Method: methodological study, with a scoping review and validation of the Bundle. Data collection took place between April and May 2022 at a university in southern Brazil. Results: nine nurses, experts in enterostomal therapy, validated the Bundle, whose items were: assessment of the skin of the obese person; hygiene care for the obese person using a medical device; nursing care for the obese person using a medical device; health education on healthy habits; continuing education on nursing care for the obese person. The items obtained a Content Validity Index ≥0.80% and 89.8% agreement. Final considerations: The Bundle can standardize nursing care, guiding, and equipping nurses with the best care intervention practices.